2001
DOI: 10.1001/archotol.127.9.1126
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Amelanotic Melanoma of the Middle Ear

Abstract: We report the first case (to our knowledge) of malignant melanoma of amelanotic type arising from the mucosa of the middle ear. An 81-year-old man who presented with right hearing loss was diagnosed as having otitis media with effusion at an otolarygology clinic. Despite subsequent treatment, he developed otorrhea and otalgia. Furthermore, a granular mass was found in the pars flaccida of the tympanic membrane. A biopsy of the mass was performed, and the findings were suggestive of malignant melanoma. The dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…CT is useful to determine the bone change, but it is difficult to make a differential diagnosis by CT alone because bone destruction is negligible and the ossicles are intact in malignant melanoma of the middle ear cavity (8). Moreover, the inferior soft-tissue resolution of CT make the diagnosis more difficult (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT is useful to determine the bone change, but it is difficult to make a differential diagnosis by CT alone because bone destruction is negligible and the ossicles are intact in malignant melanoma of the middle ear cavity (8). Moreover, the inferior soft-tissue resolution of CT make the diagnosis more difficult (5).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic MR imaging findings of high signal intensity on T1-weighted image and low signal intensity on T2-weighted image are due to higher content of melanin in the tumor (10). Conversely, in cases of an amelanotic melanoma, the signal intensity of the mass can demonstrate low signal intensity on T1-weighted images and high signal intensity on T2-weighted images (8, 11). …”
Section: Discussionmentioning
confidence: 99%
“…However, primary malignant melanoma of the middle ear mucosa is extremely rare; only six reports have been published. [6][7][8][9][10][11] Most studies have shown that radical resection of the pri-mary tumor with negative margins may provide the best therapeutic results for head and neck mucosal melanoma. However, negative margins can be very difficult to obtain due to microscopic spread that cannot be identified grossly.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Approximately 1.3 per cent of all melanomas arise within the mucosal surfaces of the body, and 55 per cent of these occur in the head and neck. 7 The treatment of mucosal melanomas is challenging.…”
Section: Discussionmentioning
confidence: 99%